Dynamics of orbits for space missions taking into account a disturbing body in an elliptical-inclined orbit: Applications to planetary moons - Dos Santos, Josuï¿½ Cardoso [UNESP]; Dos Santos Carvalho, Jean Paulo; De Moraes, Rodolpho Vilhena; De Almeida Prado, Antï¿½nio Fernando Bertachini (My University, 2015)
A classical subject of research in celestial mechanics is the study of the motion of celestial bodies under the influence of non Keplerian gravitational fields. This type of research has become important in planning future space missions that intend to send spacecrafts to orbits around planetary moons. Due to its special characteristics, some of these bodies have been object of great interest in the scientific community as potential bodies to receive these missions. Among them are some planetary moons of the Jovian system: Io, Europa, Ganymede and Callisto. Space missions that intend to orbit these bodies usually require close orbits having low eccentricities and high inclination, desired for a better coverage of the body's surface and for gravity mapping. Such missions can be planned focusing in characterizing these bodies, studying them from the surface to the atmosphere, in case of its existence. It is important to know if those bodies have liquid water beneath their surfaces, because they are potentially habitable environments. Thus, there is a great necessity for having a better comprehension of the dynamics of the orbits around these planetary moons. This comprehension is essential for the success of missions of this nature. In this context, this work aims to perform a search for low-altitude, high inclined orbits around these bodies. This study considers orbits of a spacecraft around planetary moons being perturbed by a third-body. Some applications also consider perturbations due to non-uniform distribution of mass (J2 and J3) of the planetary moon. The disturbing body is considered to be in an elliptical-inclined orbit. It is presented a model for computing the third body perturbation in which the mean anomalies of the spacecraft and the disturbing body are eliminated by means of an average technique. The Lagrange planetary equations are used to describe the orbital motion of the spacecraft around a planetary moon, taking into account the planet Jupiter as the disturbing body. Results presented here can be considered useful in studies concerning these and others planetary moons of the Solar System, with applications in astrodynamics and aerospace engineering.